CHOCOLATE AND VITAMINS - Safarova Zakiya Teshayevna; Asadova Nilufar Yorkinovna (Galaxy International Interdisciplinary Research Journal, 2022)
The article provides information about the history of the chocolate plant, its medicinal properties, general use in combination with fruits and berries, and medicinal properties. It also highlights the chemical composition of fruits and berries, various diseases and information on their prevention